Study on mosquito repellent effects and safety of basil essential oil (ocimum basilicum l. oil) on healthy volunteers - Nguyen, Thi Minh Thu; Nguyen, Duc Thanh; Doan, Minh Khiet (Tạp chí Y Dược cổ truyền Việt Nam, 2023)
Objective: To test repellent effects of basil essential oil on Aedes aegypti, Anopheles minimus and Culex tritaeniorhynchus mosquitoes on healthy volunteers. Subjects and methods: This testing was conducted according to WHO’s guidelines. A total of 1,200 mosquitoes of individual species were selected and divided in different groups of 200 mosquitoes each. Six (6) healthy volunteers including 3 males and 3 females measured their forearms and exposed those skin areas with approximately 600 cm2. The right forearms were smeared with the solvent while the left forearms were smeared with 2 ml of pure basil essential oil or a blend of essential oil - ethanol 700 (7:3). Each volunteer put their arms in the cage for 3 minutes, then counted the number of mosquitoes biting and touching the skin as well as estimated the mosquito repellant effect at the times of 0, 1, 2, 3, 4 and 6 hours after applying the testing samples. Additionally, the healthy subjects were observed and interviewed about adverse drug reactions (if any) within 6 hours of applying basil oil. Results: The test samples revealed high repellent effects on three tested mosquito species. These effect values differ insignificantly after treating samples at 1, 2, 3, 4 and 6 hours (p > 0.05). However, repellent effects at 3, 4, and 6 hours significantly decreased compared to that after immediately treating testing samples (p < 0.001). The repellent effects of both samples on Culex tritaeniorhynchus at 6 hours were significantly lower than that on Aedes aegypti and Anopheles minimus (p values < 0.05). No adverse drug reactions were observed in all 6 patients. Conclusions: Basil essential oil had high mosquito repellent effects on volunteers and no adverse drug effects.